Dora the explorer. Dora's fantastic gymnastics adventure - Nickelodeon (Firm) ([United States] : Paramount Home Entertainment, 2012)
!VAMONOS! Help Dora start the Fantastic Gymnastics show, win a ribbon with Pinto in the Big Horse Show, and find Swiper?s favorite things in these 3 big adventures!
MWT rating: NR.
DVD.
Closed-captioned.
English, French audio; French subtitles.
Keywords: Dora the Explorer (Fictitious character) -- Juvenile films; Children's television programs; Animated television programs; Television programs for the hearing impaired